Students Learning Style On Products Pastry And Bakery Learning - Baravanni, Adella Putri; Elida, Elida (Universitas Negeri Padang, 2023)
The research background from observations through the results of initial observations and interviews conducted at SMK N 6 with product pastry and bakery teacher it is known that there are still many who neglect assignments and do not understand theory well so that the value of the theory they get is very low and does not reach the KKM. The reaserach purpose is describe of students learning style on product pastry and bakery learning. This type of research is descriptive research with a quantitative approach. The population of this study were all culinary students of class XII at SMKN 6 Padang who had completed learning pastry and bakery products in class XI, totaling 94 people. The sampling technique uses a saturated sampling technique so that all populations become samples. Data collection techniques were carried out using a questionnaire with a guttman scale that has been tested for validity and reliability. Furthermore, the data were analyzed through descriptive analysis with the method of categorizing the assessment based on the average score and the percentage of the assessment. The results of the study concluded that the Learning Styles of Students in Pastry and Bakery Product Learning at SMKN 6 Padang found that the average visual learning style was 39.70% of students belonging to the low category, then the auditory learning style was 34.95% of students belonging to the low category, and the learning style kinesthetic learning is 25.35% of students belonging to the low category. This means that there are no students who 100% have only one learning style, but various. So it can be concluded that the most dominant learning style possessed by class XII students of culinary competence in learning pastry and bakery products at SMK N 6 Padang is a visual learning style.